A new treatment model for inpatient alcoholics - Kalyoncu, Ayhan; Mırsal, Hasan; Pektaş, Özkan; Şatır, Tulga; Serez, M.; Beyazyürek, Mansur (Journal of Dependence, 2000)
Alcohol Dependence and Alcohol Abuse are mental disorders with considerable high incidence among the general population. The estimated occurrence of Alcohol Related Disorders over a 1-year-period is about %7.5 in symptomatic levels. With their consequences for the family and community as well as their social, cultural, legal and political dimensions, the significance of the Alcohol Related Disorders goes far beyond their nature of being mental disorders. These aspects also justify the necessity of special treatment programs adapted to the multidimensional structure of this disorders as described above. The following article focuses on the treatment program of the Anatolia Clinic for Alcohol Related Disoreders. This program was structured by analyzing the various treatment programs throughout the world and adjusting them according to the conditions in our country.